PEMILIHAN PLATFORM SECURITIES CROWDFUNDING UNTUK PENDANAAN UMKM - Azhar, Muhammad Hafiz; Fathurrachman, Billy; Tonapa, Jennis (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022, 2022)
In Indonesia MSMEs take a big role as a driver of the country’s economy. The need of funding in MSMEs is one the important factors for the sustainability these MSMEs. The development of Fintech or Financial Technology services which is a collaboration between technology and financial systems provide convenience for MSMEs where there are many Fintechs that provide convenience in financial transactions and funding for MSMEs so they can be more aggressive in developing their business. One type of Fintech service that has recently developed in Indonesia is Crowdfunding service. Crowdfunding can be divided into 4 types based on the business aspect, namely donation-based crowdfunding, reward, lending, and equity crowdfunding. This research will discuss about Equity Crowdfunding with descriptive method and literature study. Equity Crowdfunding currently in Indonesia has developed into Securities Crowdfunding as a highly recommended funding method for MSMEs. Securities crowdfunding is an extension of Equity crowdfunding where MSMEs not only enable to issue shares but also issue bonds or sukuk to get funds from investors on the crowdfunding platform.